KESULITAN BELAJAR ANAK USIA 5-6 TAHUN DI TK LAB MODEL MUHAMMADIYAH PONTIANAK KOTA - Marwati, Sri; Yuniarni, Desni; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractLearning difficulties are a disturbance in one or more of the basic psychological processes that include understanding and use of speech or writing language.